2011
DOI: 10.1007/s11010-011-1175-9
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of thyroid hormone on post-ischemic cardiac performance: potential involvement of Akt and ERK signalings

Abstract: The present study explored the effects of thyroid hormone (TH) treatment on post-ischemic cardiac function and potential implicated mechanisms. Acute myocardial infarction (AMI) was induced in mice by coronary artery ligation while sham-operated animals served as controls. This procedure resulted in a marked depression of cardiac function and significant reduction in TH levels in plasma. TH was given at a dose aiming to normalize T3 levels in plasma [AMI-TH (A)] and also at higher doses. The group of animals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 37 publications
2
44
0
3
Order By: Relevance
“…TH induces molecular changes that benefit the failing heart, including the stimulation of pro-survival pathways such as Akt and mTOR (Mourouzis et al 2012) that is accompanied by improved cardiac function, paralleling changes induced by exercise, mediated by IGF-1 (Ojamaa 2010), to drive increases in contractile proteins critical to cardiac function and performance (Periasamy et al 2008). Exercise has also been shown to increase myocardial TR expression and T3 levels in a small cohort of HF patients with ventricular assist devices (Adamopoulos et al 2013), underscoring the role for TH in promoting positive adaptive remodeling of the injured heart.…”
Section: Discussionmentioning
confidence: 99%
“…TH induces molecular changes that benefit the failing heart, including the stimulation of pro-survival pathways such as Akt and mTOR (Mourouzis et al 2012) that is accompanied by improved cardiac function, paralleling changes induced by exercise, mediated by IGF-1 (Ojamaa 2010), to drive increases in contractile proteins critical to cardiac function and performance (Periasamy et al 2008). Exercise has also been shown to increase myocardial TR expression and T3 levels in a small cohort of HF patients with ventricular assist devices (Adamopoulos et al 2013), underscoring the role for TH in promoting positive adaptive remodeling of the injured heart.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism has been previously discussed, 20,21 and there have subsequently been several reports of their value in other "low-T 3 " conditions (euthyroid sick syndrome). [21][22][23][24][25][26][27] Hormonal therapy that included T 3 was first administered to a series of human braindead potential organ donors at Groote Schuur Hospital in 1984. 28 The initial regimen involved the hourly administration of T 3 (2μg), cortisol (100mg), and insulin (20units).…”
Section: Discussionmentioning
confidence: 99%
“…We did not differentiate between therapy with T 3 vs T 4 , but there is some experimental and clinical evidence that T 3 may be preferable to T 4 . [22][23][24][25][26][27] If all treateddonors had received T 3 , therefore, it is possible the results of heart and lung procurement would have been even better.…”
Section: Discussionmentioning
confidence: 99%
“…In animals we have shown that dosage is important: Greater doses of T3 after old infarcts were beneficial [37] however in early postinfarct rats they actually caused greater REM and CHF, associated with an overt increase of Akt, as already mentioned [22]. Ojamaa et al [38] in rats found that only higher doses (20 mg/day) increased SERCA-2α and SERCA-2α/PLB ratio and αMHC.…”
Section: The Practical Questions Of Th Administrationmentioning
confidence: 91%
“…The "nothing in excess" adage is very pertinently pictured by our finding [22] that Akt, a determining factor for the expression of psychological H, becomes deleterious when overexpressed due to high T3 doses . Accordingly, Matsui et al [23], have also shown that transgenic rats overexpressing Akt develop myocardial fibrosis.…”
Section: Some Paradigms Should Be Givenmentioning
confidence: 98%